2003
DOI: 10.1159/000074526
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Antimicrobial Agents into the Prostate

Abstract: In the present review article, the penetration of antimicrobial agents into prostatic fluid and tissue was examined. Three major factors determining the diffusion and concentration of antimicrobial agents in prostatic fluid and tissue are the lipid solubility, dissociation constant (pKa) and protein binding. The normal pH of human prostatic fluid is 6.5–6.7, and it increases in chronic prostatitis, ranging from 7.0 to 8.3. A greater concentration of antimicrobial agents in the prostatic fluid occurs in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 54 publications
2
78
0
9
Order By: Relevance
“…Furthermore, we found that up to 76.3% of the isolates showed resistance towards co-amoxiclav and that 42% isolates showed resistance to fluoroquinolones [12][13][14]. Fluoroquinolones are considered as first choice for the treatment of UTIs in men, mainly because it has advantages over co-amoxiclav, which are related to its pharmacokinetic properties [15,16]. However, observed higher percentages of resistances against both drugs indicated that they could render their efficacies as therapeutic agents, particularly in Indian sub-continent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that up to 76.3% of the isolates showed resistance towards co-amoxiclav and that 42% isolates showed resistance to fluoroquinolones [12][13][14]. Fluoroquinolones are considered as first choice for the treatment of UTIs in men, mainly because it has advantages over co-amoxiclav, which are related to its pharmacokinetic properties [15,16]. However, observed higher percentages of resistances against both drugs indicated that they could render their efficacies as therapeutic agents, particularly in Indian sub-continent.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative choice, nitrofurantoin could be considered as a drug of choice, given the low level of resistance found against this antibiotic [17]. However, there is no data on the effectiveness of this drug in the treatment of male patients and pharmacokinetic properties of this antibiotic are not better than those of fluoroquinolones [16]. Prevalence of MDR strains of UPEC was investigated in this study and it appeared that 77.5% of all the screened isolates were resistant to three or more than three of the tested antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…For organisms known to be ST131, the only conventional drugs with less than 25% resistance prevalence are ceftriaxone, imipenem, and nitrofurantoin (10), making oral doxycycline and minocycline potentially attractive alternative options. Furthermore, both doxycycline and minocycline are known to have excellent prostatic penetration, with concentrations as high as 40 to 100% and 60% of serum levels, respectively (16).…”
Section: Discussionmentioning
confidence: 99%
“…Major factors determining the penetration of antimicrobial agents into the prostatic tissue have been reported to include a high level of lipid solubility, low degree of ionization, high dissociation constant, low protein binding and small molecular size (2,6). FQs satisfy these conditions, and their use is recommended as optimal agents for the treatment of prostate infections (2).…”
Section: Discussionmentioning
confidence: 99%